2005
DOI: 10.1097/01.jcp.0000155832.79777.b5
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cytochrome P450 2D6 Genotype and Prescription Patterns of Antipsychotic and Antidepressant Drugs in Hospitalized Psychiatric Patients

Abstract: Mrs P, a 46-year-old married woman with a 9-year history of recurrent depressive illness, presented with depressed mood, 194

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
4
17
0
Order By: Relevance
“…Furthermore, other studies have also shown that CYP2D6 EMs [genotyping (two active alleles; *1, *2, *33, *35) or phenotyping (ODV/VEN ratio) determined] experienced a better clinical response to VEN than PMs; these findings suggest that the metabolism of VEN to ODV is a determinant factor for the clinical outcome [28,100,101]. Perhaps in CYP2D6 PMs the alternative metabolic pathway of VEN (N-demethylation mediated through CYP3A4, CYP2C9, and CYP2C19) may assume greater importance, which yields pharmacologically inactive or less-active metabolites.…”
Section: Genetic Biomarkers and Metabolic Phenotypesmentioning
confidence: 94%
“…Furthermore, other studies have also shown that CYP2D6 EMs [genotyping (two active alleles; *1, *2, *33, *35) or phenotyping (ODV/VEN ratio) determined] experienced a better clinical response to VEN than PMs; these findings suggest that the metabolism of VEN to ODV is a determinant factor for the clinical outcome [28,100,101]. Perhaps in CYP2D6 PMs the alternative metabolic pathway of VEN (N-demethylation mediated through CYP3A4, CYP2C9, and CYP2C19) may assume greater importance, which yields pharmacologically inactive or less-active metabolites.…”
Section: Genetic Biomarkers and Metabolic Phenotypesmentioning
confidence: 94%
“…Further work on this phenomenon is important because the literature regarding antidepressant efficacy and tolerability in CYP 2D6 PMs is limited principally to retrospective analyses 1,15 and small, prospective, studies 16 16 demonstrated that subjects heterozygous for 1 reduced-functioning allele had higher levels of S-mianserin, which was accompanied by a greater likelihood of treatment response. In this case, CYP 2D6 PMs had a greater treatment response than did CYP 2D6 EMs.…”
Section: The Case For Nortriptylinementioning
confidence: 97%
“…Several pharmacogenetic studies on antidepressant induced side effects (mouth dryness, nausea, and restlessness) reported that CPY2D6 poor metabolizers had an increased frequency and severity of concentration-dependent side effects due to slow elimination (Rau et al, 2004; D'Empaire et al, 2011). A retrospective follow-up study of depressed inpatients found that CYP2D6 poor metabolizers had more frequent switches (RR 3.50, 95% CI 1.52-8.10), and more dosage modifications (RR 2.18, 95% CI 1.36-2.95), which was indicative of an overall expression of unsatisfactory response to treatment including both treatment failure and unacceptable side effects (Mulder et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Severity of depression, maternal age, marital status (living alone or cohabiting), education level (≤12 or >12 years), race (Caucasian vs. others), body mass index (BMI, kg/m 2 ), vitamin supplement intake, and smoking status were considered as potential confounders if crude estimates resulted in p -values of less than 0.10. “Duration of antidepressant use” and “reasons for discontinuation” were not considered in the analyses given that they are intermediate variables in the causal pathway between the exposure and the outcome (Rau et al, 2004; Mulder et al, 2005; Bijl et al, 2008), and not sharing a common cause with CYP2D6 genotype (Shenfield, 2004; D'Empaire et al, 2011). …”
Section: Methodsmentioning
confidence: 99%